ARE INDONESIAN NURSES READY FOR HEALTHCARE ROBOTS DURING THE COVID-19 PANDEMIC? - Feni Betriana; Tetsuya Tanioka; Rozzano Locsin; Hema Malini; Devia Putri Lenggogeni (Belitung Nursing Journal, 2020)
Healthcare robots are used in Indonesia and other countries to combat COVID-19 pandemic. This article was aimed to describe a perspective about healthcare robots, and to recommend ways for Indonesian nurses to engage with healthcare robots during the COVID-19 pandemic. One view hindering healthcare robot appreciation as partners of nurses is its threat to their practice. However, with the current environment of COVID-19 ‘frontline’ situations, increasing infections of patients with SARS COV2, limited personal protective equipment, and the fastidious nature of maintaining social distancing and mask-wearing, it may be best to view healthcare robots as significant partners to facilitate safety, and ease the demands of nursing care activities in order to safeguard human lives while enhancing human well-being. Educating healthcare practitioners about healthcare robot programming and assurance of its safe and secure use can advance robot appreciation as partners in healthcare. These goals, challenges, and recommendations can provide Indonesian nurses some pathways-to-readiness towards a partnership involving healthcare robots, particularly during this COVID-19 pandemic, and in the future.